Faktor-Faktor yang Memengaruhi Perfoma Atlet Prestasi Olahraga Permainan Bola Kecil - Farhati, Soraya; Berawi, Khairun Nisa; Daulay, Suryani Agustina; Kurniawan, Candra (Medula, 2025)
Small ball game sports are a category of sports that involve small-sized balls and bats. Examples of these sports include badminton, rounders, baseball, softball, tennis, and others. Indonesia has not yet achieved notable achievements in small ball game sports. To improve performance and achieve better results, athletes must maintain optimal performance levels. It is crucial to identify and optimize all factors affecting the performance of small ball game athletes to help them reach their full potential. Optimal physical condition is the most essential factor for athletes. Physical fitness can be improved through the right combination of frequency, intensity, duration, and types of exercise. Another factor that affects athletic performance is nutrition, including macronutrients such as carbohydrates, proteins, and fats, as well as micronutrients like vitamins and minerals. Athletes have different nutritional needs compared to non-athletes. Furthermore, nutritional requirements vary across different sports disciplines and are highly individualized. Psychological factors also significantly affect an athlete's performance. An athlete's psychological state greatly influences their concentration during competitions and plays a crucial role in their ability to perform at their best. Key psychological aspects to consider include discipline, motivation, self-confidence, and personality. To achieve optimal performance, athletes require physical training, nutritional monitoring, and psychological support.